2007
DOI: 10.1007/s10551-007-9630-y
|View full text |Cite
|
Sign up to set email alerts
|

Gender Diversity in the Boardroom and Firm Financial Performance

Abstract: board of directors, corporate governance, endogeneity, firm value, women,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

90
1,302
12
41

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,608 publications
(1,445 citation statements)
references
References 49 publications
90
1,302
12
41
Order By: Relevance
“…This is consistent with values obtained by Campbell and Minguez-Vera (2007) for the Spanish market, Demsetz and Villalonga (2002) for the US market and Hillier and McColgan (2001) for the UK market are all greater than 1. Furthermore, Table 1 indicates that only 37.8 % of Sri Lankan listed companies have one or more female directors on their boards.…”
Section: Explanatory Variablessupporting
confidence: 91%
See 2 more Smart Citations
“…This is consistent with values obtained by Campbell and Minguez-Vera (2007) for the Spanish market, Demsetz and Villalonga (2002) for the US market and Hillier and McColgan (2001) for the UK market are all greater than 1. Furthermore, Table 1 indicates that only 37.8 % of Sri Lankan listed companies have one or more female directors on their boards.…”
Section: Explanatory Variablessupporting
confidence: 91%
“…In an investigation into Spain's listed firms, Campbell and Minguez-Vera (2007) found a positive significant relationship with female proportion on the board and the company's Tobin's Q value. Erhardt et al (2003) found that the percentage of female directors' is positively related to the larger US firms' two accounting measures: return on assets and return on investments.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The target of Malaysia is to have women's representation of 30% in senior decision-making positions and on boards by 2016 as to accelerate the development of high-potential women leaders in the labor market and in decision-making positions across all industry sectors and business functions [6]. However, Malaysia has only achieved 10.7% across all public listed companies (PLCs) and 14% for the Top 100 companies by market capitalisation according to Bursa Malaysia [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, Malaysia has only achieved 10.7% across all public listed companies (PLCs) and 14% for the Top 100 companies by market capitalisation according to Bursa Malaysia [6].…”
Section: Introductionmentioning
confidence: 99%